SOME SOCIAL-PSYCHOLOGICAL CHARACTERISTICS OF STUDENT WELFARE IN EDUCATIONAL ENVIRONMENT - Harutyunyan, N. A. (Modern Psychology, 2021)
The article is devoted to one of the most important issues in modern psychology, the issue of student well-being. The work covers a number of approaches to personal well-being through theoretical analysis, which presents the types of well-being and the ways of expression, structure and features. The author explores a number of factors, including student satisfaction with learning activities, group cohesion, and social adjustment, as well as the interrelationships between these factors. The analysis of theoretical and research results allows us to say that no matter how much a student life is subject to a certain order, it is regulated by certain rules and norms, which insures oneself from unpleasant events, however, the psychological well-being of the student in the educational social environment is mainly conditioned by the high manifestation of adaptation and cohesion, the high level of students' satisfaction with the educational activity.
Keywords: Psychological well-being; social-psychological well-being; cohesion; adaptation; satisfaction